Surviving the COVID-19 Pandemic with a Wolf Pack and the Marco Polo App - Olson Beal, Heather K. (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This narrative nonfiction essay explores the ways in which a group of academic mothers used Marco Polo, a video instant messaging app, to remain tethered to each other and to their work during the COVID-19 pandemic. The mothers, who are a combination of millennial and Gen Xers with children aged two to twenty-three, hail from a range of academic disciplines (e.g., theatre, education, environmental science, community health, counseling, psychology, and hospitality administration). We were all well into our careers and accustomed to grappling with the myriad ways in which the things we were raised to believe—that we could do anything we put our minds to and could definitely be mothers and career women—sometimes still felt like a pipe dream. And then COVID-19 came barreling into our lives, laying waste to all the usual coping and time management strategies upon which we typically rely. Since mid-March, we have exchanged an average of between fifty and seventy-five Marco Polo messages per day and have covered a wide range of topics—from spice storage methods, to preferred Cheeto shapes, to teaching our children to do long division while attending Zoom meetings, and to watching our male colleagues soar in terms of research productivity while we struggle to find five minutes of uninterrupted time to respond to an email. The essay offers some speculative ideas as to the role Marco Polo played in a larger story about connections between adult women during challenging times.